2010
DOI: 10.3382/ps.2009-00411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caponization on growth performance, carcass composition, and meat quality of medium growth broilers

Abstract: A 2-trial experiment was conducted to evaluate the effects of caponization on growth performance, carcass composition, and meat quality of medium growing broilers. Male chicks were caponized at 3 wk of age and reared until either 18 (trial 1) or 24 (trial 2) wk of age. In trial 1, the experimental groups included intact males, sham-operated chickens, and capons, whereas trial 2 comprised only intact males and capons. The concentration of testosterone was drastically reduced by caponization but remained detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 29 publications
5
35
2
4
Order By: Relevance
“…There were no sex differences for texture, confirming the results obtained by Symeon et al (2010) and Calik et al (2015) in capons with 18 and 24 weeks of age, respectively. However, Sirri et al (2009), Symeon et al (2010 and Lin et al (2011), observed that caponisation decreases texture values in capons with 180 days, 24 and 28 weeks of age, respectively. Breed differences were found and the Amarela had tougher meat than Pedrês.…”
Section: Meat Physical and Chemical Characteristicssupporting
confidence: 86%
See 2 more Smart Citations
“…There were no sex differences for texture, confirming the results obtained by Symeon et al (2010) and Calik et al (2015) in capons with 18 and 24 weeks of age, respectively. However, Sirri et al (2009), Symeon et al (2010 and Lin et al (2011), observed that caponisation decreases texture values in capons with 180 days, 24 and 28 weeks of age, respectively. Breed differences were found and the Amarela had tougher meat than Pedrês.…”
Section: Meat Physical and Chemical Characteristicssupporting
confidence: 86%
“…The effect of chicken sex and breed on physicochemical composition of breast meat (Table 2) indicates that WHC (cooking loss) and pH were not affected by sex nor breed. Miguel et al (2008) and Symeon et al (2010) in capons with 29 weeks (caponisation 8 weeks) and 18 to 24 weeks (early caponisation 3 weeks), respectively, reported that caponisation had no effects on pH and WHC. There were no sex differences for texture, confirming the results obtained by Symeon et al (2010) and Calik et al (2015) in capons with 18 and 24 weeks of age, respectively.…”
Section: Meat Physical and Chemical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report has shown that even the use of medium growing hybrids under standard commercial diets produced very heavy carcasses in ages .5 months (Symeon et al, 2010). Therefore, it seems that the use of slow-growing genotypes is the most appropriate for this particular production system.…”
Section: Introductionmentioning
confidence: 99%
“…The increased overall fatness in capons modifies meat quality characteristics as well (Symeon et al, 2010). Moreover, it enhances flavor, texture and meat juiciness when compared with intact cockerels (Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%